Passive monetary policy and active fiscal policy in a monetary union - Bartosz Maćkowiak; Sebastian Schmidt (European Central Bank (ECB), 2023)
How is the price level determined in a monetary union when the common monetary policy pegs the nominal interest rate? How are the price levels in the member countries determined? We extend the fiscal theory of the price level to the case of a heterogenous monetary union. Price level determinacy follows if fiscal policy at the level of the union as a whole is active. Different combinations of national fiscal policies and a common fiscal policy with "Eurobonds" amount to active fiscal policy for the union, but can have very different implications for the effects of fiscal and monetary policy. We propose how to coordinate the national policies and the common policy for union-wide policy to be active.
Keywords: E31; E63; F45; 330; fiscal theory of the price level; monetary union; fiscal rules; Eurobonds